2019
DOI: 10.1016/j.jmig.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Harassment and Discrimination in Gynecology: Results of the AAGL Member Survey

Abstract: To characterize workplace and sexual harassment and discrimination among physicians in gynecology. Design: A beta-tested Internet survey was distributed by e-mail using the REDCap platform. All responses were anonymous. Setting: The survey was distributed to the 7026 physician members of an international gynecologic society (AAGL), including faculty and trainees. Patients: Not applicable. Interventions: The survey was distributed on 3 occasions between July and September 2018. The survey contained questions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 14 publications
0
37
0
3
Order By: Relevance
“…The authors noted that female compared to male grant recipients were more likely to report sexual harassment and to report perceptions and experiences of gender bias. Another study on experiences and perceptions among gynecologic surgeons found that over two-thirds of women and 40% of men had reported workplace discrimination, and more than half of women and 20% of men had reported workplace harassment [13]. Banerjee and colleagues examined these issues among European oncologists [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors noted that female compared to male grant recipients were more likely to report sexual harassment and to report perceptions and experiences of gender bias. Another study on experiences and perceptions among gynecologic surgeons found that over two-thirds of women and 40% of men had reported workplace discrimination, and more than half of women and 20% of men had reported workplace harassment [13]. Banerjee and colleagues examined these issues among European oncologists [14].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that 58% of female faculty had experienced some form of sexual harassment in the work environment [6]. Although several groups have closely looked at sexual harassment and gender-related bias in specific fields of medicine [7][8][9][10][11][12][13][14], outside of personal anecdotes, few studies have investigated the prevalence of this problem in the field of medicine devoted to the diagnosis and treatment of women's cancers-gynecologic oncology.…”
Section: Introductionmentioning
confidence: 99%
“…For example, all female third-year medical students in a longitudinal qualitative study noted that they accepted inequities between men and women simply because "that's the way things are" [35]. A 2019 retrospective study demonstrated that over half of female OB/Gyn physician respondents reported workplace harassment, with the most prevalent consequence being a loss of confidence [36,37]. Acknowledging that OB/Gyn is a predominately female-driven field, the reported instances of sexual harassment in predominately male-driven fields, such as general surgery, plastic surgery, and thoracic surgery, were 43%, 36%, and 81%, respectively [34,38,39].…”
Section: Discrimination Bias and Harassmentmentioning
confidence: 99%
“…Congratulations to Dr. Brown and colleagues for shedding light where shame and secrecy would otherwise hide harassment and workplace bias in obstetrics and gynecology [1]. The survey responses tell a sobering but not unexpected story.…”
mentioning
confidence: 96%